Prevalence of child marriage and its impact on fertility outcomes in 34 sub-Saharan African countries - Sanni Yaya; Emmanuel Kolawole Odusina; Ghose Bishwajit (BMC, 2019)
Abstract Background The issue of child marriage is a form of human rights violation among young women mainly in resource-constrained countries. Over the past decades, child marriage has gained attention as a threat to women's health and autonomy. This study explores the prevalence of child marriage among women aged 20-24 years in sub-Saharan Africa countries and examines the association between child marriage and fertility outcomes. Methods Latest DHS data from 34 sub-Saharan African countries were used in this study. Sixty thousand two hundred and fifteen women aged 20-24 years were included from the surveys conducted 2008-2017. The outcome variables were childbirth within the first year of marriage (early fertility), first preceding birth interval less than 24 months (rapid repeat of childbirth), unintended pregnancy, lifetime pregnancy termination, the use of modern contraceptive methods, lifetime fertility and any childbirth. The main explanatory variable was child marriage (< 18 years) and the associations between child marriage and fertility outcomes were examined from the ever-married subsample to estimate odds ratios (ORs) and 95% CIs using binary logistic regression models. Results In the study population, the overall prevalence of women who experience child marriage was 54.0% while results showed large disparities across sub-Saharan African countries ranging from 16.5 to 81.7%. The prominent countries in child marriage were; Niger (81.7%), Chad (77.9%), Guinea (72.8%), Mali (69.0%) and Nigeria (64.0%). Furthermore, women who experience child marriage were 8.00 times as likely to have ≥3 number of children ever born (lifetime fertility), compared to women married at ≥18 years (OR = 8.00; 95%CI: 7.52, 8.46). Women who experience child marriage were 1.13 times as likely to use modern contraceptive methods, compared to adult marriage women (OR = 1.13; 95%CI: 1.09, 1.19). Those who married before the legal age were 1.27 times as likely to have lifetime terminated pregnancy, compared to women married at ≥18 years (OR = 1.27; 95%CI: 1.20, 1.34). Also women married at < 18 years were more likely to experience childbirth, compared to women married later (OR = 5.83; 95%CI: 5.45, 6.24). However, women married at < 18 years had a reduction in early childbirth and a rapid repeat of childbirth respectively. Conclusion Implementing policies and programmmes against child marriage would help to prevent adverse outcomes among women in sub-Saharan Africa. Also, social change programmes on child-marriage would help to reduce child marriage, encourage the use of modern contraceptive, which would minimize lifetime terminated pregnancy and also children ever born.